Can we link emotional eating with the emotion regulation skills of adolescents?. Issue 7 (2nd July 2016) - Vandewalle, Julie; Moens, Ellen; Beyers, Wim; Braet, Caroline
Abstract : Objective: A recent cross-sectional study showed that maternal rejection is associated with emotional eating of obese youngsters seeking treatment, and that this relation is mediated by maladaptive emotion regulation (ER) of the youngsters. We wanted to build on this study and investigate the relation between parental rejection, maladaptive ER and emotional eating in a community sample using longitudinal data. Design: Participants were 81 youngsters between the ages of 10 and 16 years. Participants completed questionnaires assessing maternal and paternal rejection, ER strategies and emotional eating, at two time moments ( M  = 71 days between time moments). Latent change models were used to estimate level and change of each variable. Results: Results showed that the levels of maternal rejection, maladaptive ER and emotional eating were related. The indirect effect of the level of maternal rejection on the level of emotional eating through the level of maladaptive ER was marginally significant. On average, maternal rejection showed no change over time, whereas the other variables decreased. The changes in the variables were not related. Conclusion: The findings highlight the importance of assessing the emotional bond between mother and youngster and the ER of youngsters with an emotional eating style.